Polymorphisms of interleukin 6 in Down syndrome individuals: a case-control study - Mattos, M. F.; Uback, L.; Biselli-Chicote, P. M.; Biselli, J. M. [UNESP]; Goloni-Bertollo, E. M.; Pavarino, E. C. (Funpec-editora, 2017)
Down syndrome (DS) individuals present impaired adaptive immune system. However, the etiology of the immunological deficiency in these individuals is not completely understood. This study investigated the frequency of interleukin 6 polymorphisms (rs1800795, rs1800796, and rs1800797) in individuals with DS and individuals without the syndrome. The study included 282 individuals, 94 with DS attended at the General Genetics Outpatient Service of Hospital de Base, Sao Jose do Rio Preto, SP, Brazil, and 188 individuals without DS attended at the Pediatric Service of Hospital de Base de Sao Jose do Rio Preto, SP, Brazil. Genotyping was performed by allelic discrimination technique by real-time polymerase chain reaction using TaqMan SNP Genotyping Assays (Applied Biosystems). There was no difference in the genotype frequency between individuals with and without DS for the evaluated polymorphisms (P > 0.05). The frequency of interleukin 6 polymorphisms did not differ significantly between individuals with and without DS in the casuistic analyzed.
Keywords: Down syndrome; Trisomy 21; Genetic polymorphism; Interleukin 6